Advertising management - Jaishri Jethwaney (Oxford University press, 2012)
The book explores the core concepts of advertising through practical applications, taken particularly from the Indian business environment. It covers theoretical foundations of advertising, brand building through advertising, campaign execution and agency relationships, and the use of marketing research techniques for developing and evaluating marketing strategies.